ORTAOKUL 8. SINIF ÖĞRENCİLERİNİN MATEMATİK ÖZ YETERLİK ALGILARI VE MATEMATİK BAŞARI PUANLARI ARASINDAKİ İLİŞKİNİN İNCELENMESİ - UÇAR, ŞEYMA ŞEMSİ (Fırat Üniveristesi, 2025)
Bu araştırmanın amacı, 8. sınıf öğrencilerinin matematik öz yeterlik algıları ve matematik başarı puanları arasındaki ilişkileri incelemektir. Araştırma ilişkisel tarama modeli çerçevesinde yürütülmüş olup, araştırmanın örneklemi 2024-2025 eğitim-öğretim yılında Malatya il merkezindeki devlet ortaokullarında öğrenim gören 605 öğrenciden oluşturulmuştur. Araştırmada veri toplama aracı olarak Kişisel Bilgi Formu, Matematik Öz Yeterlik Algısı Ölçeği kullanılmıştır. Verilerin analizinde çarpıklık ve basıklık testi, Bağımsız Gruplar T-testi, Anova testi, Pearson Momentler Çarpım Korelasyon analizi ve Doğrusal Regresyon analizi uygulanmıştır. Araştırma bulgularına göre, öğrencilerin matematik öz yeterlik algılarının orta düzeyde olduğu belirlenmiştir. Matematik öz yeterlik algısı cinsiyet, aile gelir düzeyi ve karne notuna göre anlamlı farklılıklar göstermiştir. Matematik öz yeterlik algısı ile matematik başarısı arasında orta düzeyde pozitif yönde anlamlı ilişki vardır. Doğrusal regresyon analizi sonuçlarına göre, matematik öz yeterlik algıları matematik başarı puanının anlamlı bir yordayıcısıdır. Elde edilen bulgular doğrultusunda, eğitim programlarında öğrencilerin öz yeterlik algılarını güçlendirmeye yönelik çalışmalara yer verilmesi önerilmiştir. Anahtar Kelimeler: İlişkisel Tarama Modeli, Matematik Başarısı, Matematik Öz Yeterlik, Matematik Öz Yeterlik Algısı

The purpose of this study is to examine the relationships between 8th-grade students' perceptions of mathematics self-efficacy and their mathematics achievement scores. The study was conducted using a relational screening model, and the study group consisted of 605 students enrolled in public middle schools in the Malatya city center during the 2024-2025 academic year. A Personal Information Form and the Mathematics Self-Efficacy Perception Scale were used as data collection tools. Skewness and kurtosis tests, Independent Samples T-tests, ANOVA tests, Pearson Product-Moment Correlation Analysis, and Linear Regression Analysis were used in data analysis. According to the research findings, it was determined that the students' perceptions of mathematics self-efficacy were at a moderate level. Perceptions of mathematics self-efficacy differed significantly according to gender, family income level, and report card grade. There is a moderately positive and significant relationship between perceptions of mathematics self-efficacy and mathematics achievement. According to the linear regression analysis results, perceptions of mathematics self-efficacy are a significant predictor of mathematics achievement scores. In line with the findings, it was suggested that studies aimed at strengthening students' self-efficacy perceptions should be included in educational programs. Key Words: Relational Screening Model, Mathematics Achievement, Mathematics Self-Efficacy, Perception of Mathematics Self-Efficacy
Examining the relationship between secondary school 8th grade students' mathematics self-efficacy perceptions and mathematics achievement scores
Keywords: Eğitim ve Öğretim